Applying extended urban metabolism approach and sustainability indicators for the slum upgrading in Barangay Kamuning, Quezon City - Castillo, Airish; Fontanoza, Franklin Jr. S. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
In the 1970s, the slum upgrading approach was embraced by the Philippine government in response to the shelter dilemma facing the urban poor. However, rapid urbanization has led to the proliferation of slum areas in major cities, including Quezon City. One of the significant slum areas in the city is found in Barangay Kamuning, specifically the Bernardo Park area where this thesis is focused on. Meanwhile, cities nowadays including slum settlements are based on linear metabolisms contributing to different impacts such as the high dependency on non-renewable ones. In this context, this thesis aims to apply the Extended Urban Metabolism & Sustainability Indicators to seek spatial planning solutions to improve living conditions of dwellers in Barangay Kamuning’s slum settlement.
The sequential explanatory approach was used in the study with quantitative approach (i.e. Life Cycle Assessment) being the first stage of data collection then supported by the qualitative approach (i.e. in-depth semi structured interviews with stakeholders to make the study as participatory as possible). The gathered data was used in generating plans to be applied elsewhere in the city or in other slum settlements with similar landscape characteristics. The study's findings reveal the environmental impact of Quezon City's metabolism, with depletion of abiotic resources, particularly fossil fuels, was identified as the most significant impact category. The identified categories then served as Sustainability Indicators, enabling targeted interventions to enhance the city's environmental sustainability with the aim of improving the liveability conditions of slum dwellers. The study's assessment provides valuable insights for policymakers, urban planners, and relevant stakeholders in prioritizing efforts towards a more sustainable city metabolism in slum upgrading.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: City planning -- Kamuning (Quezon City).; Slums -- Kamuning (Quezon City).; Sustainability -- Kamuning (Quezon City).; Urban renewal -- Kamuning (Quezon City).